2019
DOI: 10.1007/s11695-019-04115-9
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Fetal Adipose Tissue Thickness in Pregnancies After Gastric Bypass Surgery

Abstract: Purpose Recent studies showed that women after surgery are at higher risk of delivering small-for-gestational infants. Thus, this study aims to investigate longitudinal changes of fetal subcutaneous adipose tissue thickness (FSCTT) of fetuses conceived after gastric bypass surgery as compared to BMI-matched controls. Methods Retrospective cohort study measuring ultrasound-derived longitudinal trajectories of abdominal FSCTT in 41 singleton pregnancies after gastric bypass surgery compared to 41 BMI-matched con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
(30 reference statements)
0
6
1
Order By: Relevance
“…However, the growth pattern of other fetal growth parameters in this study, such as the AC, showed only marginal differences. This is in contrast to previous observations but may be a consequence of the lower sample size in this very special study population [5,6]. While a causal relationship between glycemic alterations and fetal development is obvious, we are convinced that the intrauterine growth restriction in twins in women with history of GB surgery is more complex and subject to other additional processes as it is for singletons.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…However, the growth pattern of other fetal growth parameters in this study, such as the AC, showed only marginal differences. This is in contrast to previous observations but may be a consequence of the lower sample size in this very special study population [5,6]. While a causal relationship between glycemic alterations and fetal development is obvious, we are convinced that the intrauterine growth restriction in twins in women with history of GB surgery is more complex and subject to other additional processes as it is for singletons.…”
Section: Discussioncontrasting
confidence: 89%
“…Longitudinal assessment of ultrasound-derived FSCTT was performed retrospectively from the second trimester onward after recalibration of the image. For that purpose, the abdominal circumference level (AC) has been used for all measurements since it is a standardized cutting plane (according to ISUOG guidelines) [13], for unification and therefore having a continuity and equality within the measurements as reported in our previous study [6] with measure points of FSCTT (measured in millimeters [mm] between the outer and inner margin of the echogenic subcutaneous tissue after magnifying the area of interest) on (i) the anterior abdominal wall in front of the intrahepatic tract of the umbilical vein, (ii) on the left side next to the stomach, and (iii) on the exact opposite right side of the abdomen. Medical records were used to collect data on BMI before pregnancy or before bariatric surgery and time between operation and pregnancy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fetal subcutaneous tissue thickness was measured in millimeters at the level of the abdominal plane at three different points after magnification of the region of interest, from the outer to the inner margin of the echogenic fetal subcutaneous tissue: (i) at the level of the left lateral abdominal wall near the stomach, (ii) at the level of the right lateral abdominal wall symmetrically to the left side caliper, (iii) anterior as near as possible to the umbilical vein entrance into the abdomen. For the analysis, we considered the mean value of the three measurements for each fetus if available 15 …”
Section: Methodsmentioning
confidence: 99%
“…For the analysis, we considered the mean value of the three measurements for each fetus if available. 15 …”
Section: Methodsmentioning
confidence: 99%